Exponential synchronization for delayed reaction-diffusion neural networks through hybrid coupling - Xiwei Liu; Jinglong Wu (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
This paper investigates the global exponential synchronization (GES) for coupled reaction-diffusion neural networks (RDNNs) with coupling delay via hybrid coupling. In our model, the coupling matrix can be asymmetric and irreducible. The hybrid coupling means that: spatial coupling (SPC) and state coupling (STC) can both exist. On the one hand, we redesign the SPC protocol, which is different from other papers in this literature and can expedite the synchronization process. On the other hand, sufficient criteria of GES for this new network model are obtained by a rigorous proof. Finally, some numerical simulations are displayed to show the validity of our theory.